KONSTRUKSI PENGETAHUAN TENTANG SHOLAWAT PADA ANGGOTA PENGAJIAN SHOLAWAT â€œBHENNINGâ€ SITUBONDO - Islamiyah, Shofiatul; Mulyono, Joko (Jurnal ENTITAS SOSIOLOGI, 2019)
This study explains the construction of knowledge among Bhenning Sholawat Community prayer in Situbondo. By using the theory of social construction, this research explains the formation of a society based on the Bhenning prayer's experiences. The Qualitative Research Methods used for this study. Interviewed was done to young Bhenning prayers. The result of this study is Bhenning prayers change their bad behavior into good behavior through three simultaneously moments after joined Bhenning Sholawat Community. The Prayers have many reasons in joining Bhenning Sholawat community, which were they want to learn about theatre; because they were fascinated by Karisma Kyai Aza Ibrahimy, consideration of the many knowledge gained, the devotion to Allah Subhanahu wata'ala, and follow their friends.  Keywords: Recitation of